If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + -1y = 9 Solving -3 + -1y = 9 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1y = 9 + 3 Combine like terms: -3 + 3 = 0 0 + -1y = 9 + 3 -1y = 9 + 3 Combine like terms: 9 + 3 = 12 -1y = 12 Divide each side by '-1'. y = -12 Simplifying y = -12
| (3y/2a)/(8a^2y5/15y) | | 6x^2+2x-58=0 | | 2.3x-9.34=6.3 | | 4/17(x)=20 | | 3x-14=2x+19 | | -40-3x=14-10x | | 3-2(1/7) | | 8c+c=27 | | -4y-2+3y+4=-5 | | 24w^9x^6y-22x^4y^6= | | 2(1/7) | | 1x-6=3x-4 | | -[4(7)+2]-[3(7)-4]=x | | 4b+29=48 | | -[4(7)+2]-[3(7)-4]=-5 | | 3-21/7 | | y=3x+6graph | | 60=-5x+9 | | -(4y+2)-(-3y-4)=-5 | | 4+4y=8 | | 0=16t^2-30t+13 | | 6x-59=4x-9 | | 1+4y=8 | | 3(x+4x)=30-10x | | -2(10)+4=-8 | | 0=45-5t-5t^2 | | h=45-5t-5t^2 | | 59b^2+b=1 | | 16-5=14-10x | | (-2/5)x=8/15 | | 3(-3+0.3333333333y)-y=-9 | | -4.2=3x+25.8 |